Analisis Konsep Bank Sentral Dalam Penerbitan Uang Baru Untuk Mencegah Pemalsuan Uang Pada Jasa Penukaran Uang Pinggir Jalan di Saat Hari Raya - Saqina Maulita Pradewi; Ananda Dheya Septy; Atalia Martha Puspita (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Money changers are also increasingly developing not only in banks as official exchange places. On the eve of the holidays, some traders sell money on the side of the road. There is a phenomenon where money becomes something that is traded in the form of money exchange that often occurs before the holidays. This research uses a qualitative method. By using a qualitative approach, researchers can focus on attention and also natural events that occur. This research examines how the concept of central bank concept analysis in the issuance of new money to prevent counterfeiting of money on roadside money exchange services during the holidays. The conclusion is that transactions that always occur before the holidays with money exchange are considered violating the law because they do not comply with the standards of exchange transactions, which should always have goods traded rather than money.